Sri Lanka : Poverty Assessment - World Bank (Washington, DC, 2013)
This Poverty Assessment report reviews the evolution, and nature of poverty in Sri Lanka, by examining why its significant, recent economic downturn contrasts sharply with its considerable, economic advances during the 1960s; why poverty fell rapidly, and to a relatively, low level in some areas, though it remained high in other parts of the country; and, whether the large resources given to re-distributive programs, really helped reduce poverty. In response, Sri Lanka's hesitant attitude towards progressive economic, and social policies is seemingly the answer, for these policies would have removed the regulations that hinder effective markets, and the private sector, and, would have provided needed infrastructure, and social services, accommodating diversity within its social policies, through resources, and opportunities for the poorest. Notwithstanding gradual, economic liberalization, the economy is still more protected than in countries which started liberalization much later. The regulatory environment - particularly restrictions on labor, and land markets - and weak competitive financial markets, make the investment climate less friendly than that of competitors in the East. Regarding the role of the state in the economy, still large shares in the banking system, insurance industry, power, and water utilities, among others, are government owned. In terms of social policies, the country has a long tradition of protecting acquired rights, and encouraging patronage, rather than stimulating market-based creation of opportunities. The report stipulates the need for creating a policy environment that facilitates poverty reduction, through a strong fiscal policy, deregulation and privatization, agricultural growth policies, and labor market flexibility, based on public services that reach the poor, i.e., improved quality of education, effective social safety nets, and transparent public administration.